Removal of Multiple Keratocystic Odontogenic Tumors in a Nonsyndromic Patient - Vasconcelos, Artur Cunha (Ann Maxillofac Surg, 2017)
Multiple keratocystic odontogenic tumors are one of the key features of Gorlin–Goltz syndrome. A 15-year-old nonsyndromic female child presented with multiple keratocystic odontogenic tumors. The presence of the tumors was observed in immunological examinations. The images led to the suspicion of Gorlin–Goltz syndrome which was discarded after analyzing the patient's medical history and complementary examinations. Le Fort I osteotomy was opted to access the maxillary tumors favoring visibility and allowing simultaneous bilateral accesses. A sagittal vestibular incision in the lower rim was performed to access the mandibular lesions. After 3 months, the patient underwent a bilateral myotomy to reduce the volume of the masseter muscles. The occurrence of nonsyndromic multiple keratocystic odontogenic tumors is rare. Clinicians facing this situation shall seek for other known features of the Gorlin–Goltz syndrome and follow up closely these patients for the possibility of occurrence of basal cell carcinoma.